Análisis de sostenibilidad que la empresa pública municipal de agua potable y alcantarillado del cantón Mejía (EPAA-Mejía, EP), ha tenido desde el inicio de sus funciones en el año 2012 hasta el año 2015 - Pazmiño Paneluisa, Jorge Paúl (2018)
In the present test the analysis of the development Empresa Pública Municipal de Agua Potable y Alcantarillado del Cantón Mejía, was carried out, from its creation in 2012 until the year 2015. The analysis was made from the point of view of business sustainability. Using the Global Reporting Initiative (GRI) tool, the same tool that allows a company to evaluate sustainability matters, through economic, environmental and social performance indicators, this does not allow it to have a broad management vision of this public company, and its contribution to sustainable development in the Mejía Canton, as well as in the improvement of the quality of life and Multidimensional Poverty Indices.